PENGARUH BAURAN PEMASARAN DAN BRAND IMAGE TERHADAP KEPUTUSAN MENGINAP DI HOTEL GRAN PURI MANADO - Helni Desty Yanice. Lagarense; Jelly Netty Sendow; Stanzche Grachia Lasoma (Jurnal Hospitaliti, 2025)
This study aims to analyze the influence of marketing mix consisting of promotion, price, place, and people as well as brand image on consumer decisions to stay at Hotel Gran Puri Manado. In a highly competitive hospitality industry, understanding the factors that influence consumer decision-making is essential to improving competitiveness and customer loyalty. This study uses a quantitative approach with a survey method. Data were collected through questionnaires distributed to 50 respondents who are guests or have stayed at Hotel Gran Puri Manado. The analysis technique used is multiple linear regression analysis to determine the simultaneous and partial effects of marketing mix and brand image on the decision to stay. The results show that marketing mix has a positive and significant effect on stay decisions with t value 27.126 > t table 2.014. Brand image also has a positive and significant effect with t value 2.921 > t table 2.014. Simultaneously, both variables have a significant effect with F value 13.473 and significance 0.000 < 0.05. The Adjusted R Square value of 0.888 indicates that 88.8% of the variation in stay decisions can be explained by marketing mix and brand image variables. Based on these findings, it is recommended that the management of Hotel Gran Puri Manado continue to strengthen its marketing mix strategies and build and maintain a positive brand image to increase customer interest and loyalty. Keywords: marketing mix, brand image, stay decision, hotel, tourism